Audionarratology lessons from radio drama - Bernaerts, Lars 1980-; Mildorf, Jarmila
"Explores how radio dramas such as I Love a Mystery and The Hitchhiker's Guide to the Galaxy construct narrative through sound, music, language, and voice"--Provided by publisher.
aIntroduction: When sounds make stories: lessons for narrative theory from the study of radio drama / Lars Bernaerts and Jarmila Mildorf -- Part I: Narratological challenges in theory and practice. The audio dramatist's critical vocabulary in Great Britain / Tim Crook -- "Stage" directions in the radio script: a transgeneric narratological approach / Janine Hauthal -- Narrative mediation and the case of audio drama / Lars Bernaerts -- Earwitnessing: focalization in radio drama / Siebe Bluijs -- Simultaneity and the soundscapes of audio fiction / Caroline A. Kita -- Part II: Narrative genres and narrative experiments in audio drama. "There ain't no sense to nothin'": serial storytelling, radio consciousness, and the gothic of audition / Harry Heuser -- Auricularization and narrative-epistemic stance in Louis Nowra's Echo point / Jarmila Mildorf -- "Arthur lolled": audiophony and humor in The Hitchhiker's guide to the galaxy / Olivier Couder -- Gargantuan adaptations: narrative and non-narrative soundscapes in English and German radio plays and radio operas based on Franc?ois Rabelais and Johann Fischart / Till Kinzel -- Music, voice, and (de)narrativization in Samuel Beckett's radio play Cascando / Pim Verhulst -- Coda: Radio drama between mimetic and diegetic presentation / Marie-Laure Ryan.
aNM Glova (Recommending faculty) AY 2022-2023
aIncludes bibliographical references and index.
Keywords: Radio plays -- History and criticism; Narration (Rhetoric)